Inflammatory aorta in Giant Cell Arteritis disease: a case study of 5 patients - I. Chabchoub; M. Snoussi; F. Frikha; C. Dammak; S. Marzouk; Z. Bahloul (Sri Lanka College of Internal Medicine, 2023)
Introduction: Aortitis defined as the inflammation of the aortic wall can be due to various diseases including giant cell arteritis (GCA). Aortic involvement in GCA, reported since 1940, is rarely described. The main objective of this study was to analyse the epidemiological, clinical, radiological and evolutionary characteristics of patients with inflammatory aortitis in a cohort of patients diagnosed with GCA. We conducted a review of the literature to study the clinical and paraclinical aspects of this entity and to describe a diagnostic and therapeutic approach to inflammatory aortitis in GCA. Methods: This is a retrospective descriptive study of 109 patients with giant cell arteritis fulfilling the diagnostic criteria established by the American College of Rheumatology (ACR), conducted over a period of 25 years (1996-2020) in the internal medicine department in Hedi Chaker University Hospital, Sfax, Tunisia. The diagnosis of inflammatory aortitis was made on the basis of aortic tomography. Results: Five patients out of 109 (4.5%) had an aorta authenticated by aortic tomography. They were 2 men and 3 women with an average age of 64.2 years. The aortitis was revealed by non-specific systemic signs in all cases, namely fever, a biological inflammatory syndrome and abdominal pain in 1 patient. Clinical examination revealed a vascular murmur in one patient. A biological inflammatory syndrome (BIS) was present in all cases. Aortic involvement was discovered at the time of diagnosis of GCA in all cases. It was detected by thoracoabdominal aortic tomography in all cases and aortic MRI in one case. It involved the thoracoabdominal aorta in 4 cases and the abdominal aorta in one case. Treatment was based on high-dose corticosteroid therapy combined with an antiplatelet agent in the five patients. The evolution was marked by the achievement of apyrexia and regression of the BIS in all cases. A radiological check-up was carried out in only one patient, initially showing a stable appearance and then partial regression of the thoracoabdominal aorta at 6 and 18 months respectively. Conclusion: Inflammatory involvement of the aorta in giant cell arteritis. remains a serious and potentially life-threatening complication in the case of aneurysm rupture or aortic dissection. Initially, the diagnosis may be difficult due to the non-specific clinical presentation. Systematic screening for this condition by aortic tomography is increasingly recommended. Prompt intensive drug treatment based mainly on corticosteroids may reduce short and long-term morbidity.